A brazing connection method for tungsten alloy and molybdenum alloy

By using a brazing method of using a specific composition of brazing material and a metal foam nickel intermediate layer, the problem of low welding strength of tungsten alloy and molybdenum alloy is solved, and higher welding strength and toughness are achieved.

CN119634867BActive Publication Date: 2025-04-29CITIC HEAVY INDUSTRIES CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510185766.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-29
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

In the prior art, the welding strength of tungsten alloy and molybdenum alloy is relatively low, and the joints exhibit brittle fracture characteristics.

Method used

A brazing connection method is adopted, using solder material mainly composed of NirestTiaZrbCrcCud, and a metal foam nickel intermediate layer is added during the brazing process, and welding is carried out through a vacuum brazing furnace, and the heating and cooling rate is controlled to improve welding strength.

Benefits of technology

The welding strength of tungsten alloy and molybdenum alloy is significantly improved, the toughness and strength of the joints are improved, residual stress is reduced, and the fracture position is changed to the brazing joint area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119634867B_ABST
    Figure CN119634867B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of brazing, and specifically discloses a brazing connection method for tungsten alloy and molybdenum alloy, which includes the following steps: S1: Pretreat the tungsten alloy base material and the molybdenum alloy base material; S2: Place the brazing filler metal between the tungsten alloy base material and the molybdenum alloy base material, and place nickel foam between the brazing filler metal and the molybdenum alloy base material, and obtain a pre-brazed assembly after compaction; wherein, the composition of the brazing filler metal is Ni rest Ti a Zr b Cr c Cu d ; S3: Place the pre-brazed assembly in a vacuum brazing furnace for brazing treatment. On the basis of the conventional Ni-Ti brazing filler metal, the present invention adds Cu, Cr and Zr elements, which can improve the plasticity and toughness and mechanical properties of the joint. At the same time, adding a metal nickel foam intermediate layer during the brazing process can absorb residual strain energy, refine the shunt brazing filler metal, and also change the microstructure and form a stable structure, significantly improving the mechanical properties of the joint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing, and in particular to a brazing connection method for tungsten alloy and molybdenum alloy. Background Art

[0002] Tungsten alloy is an alloy composed of tungsten as the matrix, with a small amount of other elements such as nickel (Ni), iron (Fe), copper (Cu), cobalt (Co), molybdenum (Mo), etc. Tungsten alloy has an ultra-high melting point, which can be as high as 3422℃. This property enables it to maintain a stable physical form in a high temperature environment and is not easy to melt and deform. Therefore, in the aerospace field, it is often used to manufacture high-temperature parts of engines, such as turbine blades, combustion chambers, etc.

[0003] Molybdenum alloy is a non-ferrous alloy composed of molybdenum as the matrix and other elements such as titanium (Ti), zirconium (Zr), hafnium (Hf), tungsten (W) and rare earth elements. The expansion coefficient of molybdenum alloy is low, similar to the glass used in electron tubes. This property makes the size of molybdenum alloy change very little in an environment with large temperature changes, and it can maintain good stability. In the field of aerospace, aircraft will experience huge temperature changes during flight. Parts made of molybdenum alloy can maintain accuracy and performance under such extreme conditions, ensuring the safe and reliable operation of aircraft.

[0004] As a key means of connecting materials, welding technology plays a decisive role in giving full play to the performance advantages of tungsten alloy and molybdenum alloy. In practical engineering applications, it is often necessary to connect tungsten alloy and molybdenum alloy parts of different shapes and sizes together to meet the design requirements of complex structures. Through welding, a firm bond between components can be achieved to ensure the integrity and mechanical properties of the structure. Commonly used brazing fillers for welding tungsten alloy and molybdenum alloy include Ag-based brazing fillers, Au-based brazing fillers, Ti-based brazing fillers and Ni-based brazing fillers. Among them, Ag-based fillers are difficult to effectively wet the molybdenum alloy matrix and are not suitable for high-temperature environments; Au-based brazing fillers are not only expensive, but also the Au in the brazing filler does not react with the Mo matrix. Therefore, Ti-based brazing fillers and Ni-based brazing fillers have become more commonly used choices. Ni has good resistance to neutron irradiation and is suitable for brazing of nuclear energy equipment. The joints obtained using Ti-based or Ni-based brazing alloys usually have high connection strength and good corrosion resistance. In addition, in high-temperature application scenarios, Ti-based or Ni-based alloys also show obvious advantages as brazing fillers. In the prior art, Ti-Ni eutectic brazing filler metal is often used to braze molybdenum alloy and tungsten alloy. The optimal brazing temperature is kept for 10 minutes, and the room temperature shear strength of the sample is about 120 MPa. The fracture positions are all located on the molybdenum alloy side. The fracture is mainly due to the elongated grain structure of the hot-rolled molybdenum alloy parallel to the surface, and the strip-shaped Ti-Ni intermetallic compound formed by intergranular penetration during the brazing process causes the fracture, and the joint shows obvious brittle fracture characteristics. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problem of low welding strength of tungsten alloy and molybdenum alloy and to provide a brazing connection method of tungsten alloy and molybdenum alloy.

[0006] In order to solve the above technical problems, the present invention adopts a technical solution: a brazing connection method of tungsten alloy and molybdenum alloy, comprising the following steps:

[0007] S1: pre-treating tungsten alloy base material and molybdenum alloy base material;

[0008] S2: placing the brazing filler metal between the tungsten alloy matrix and the molybdenum alloy matrix, placing the nickel foam between the brazing filler metal and the molybdenum alloy matrix, and compacting them to obtain a pre-brazed assembly;

[0009] Among them, the composition of the brazing material is Ni rest Ti a Zr b Cr c Cu d , 15≤a≤18wt%; 10≤b≤11wt%; 11≤c≤12wt%; 14≤d≤15wt%; the rest is Ni;

[0010] S3: Place the pre-brazed assembly in a vacuum brazing furnace at a vacuum degree of 5.0×10 -4 Pa, heat up to 550-650℃ at a heating rate of 8-12℃ / min and keep warm for 5-10min, then heat up to brazing temperature at a heating rate of 4-6℃ / min and keep warm for 5-10min, then cool to 90-110℃ at a cooling rate of 8-12℃ / min, and finally cool to room temperature with the furnace to complete the brazing connection of tungsten alloy and molybdenum alloy.

[0011] As a further optimization of the brazing connection method of a tungsten alloy and a molybdenum alloy of the present invention: the step S1 is specifically: the welding surfaces of the tungsten alloy base material and the molybdenum alloy base material are polished with sandpaper, and then the polished base materials are immersed in anhydrous ethanol for ultrasonic cleaning for 25 to 35 minutes, and finally air-dried.

[0012] As a further optimization of the brazing connection method of a tungsten alloy and a molybdenum alloy of the present invention: the brazing material in step S2 is a foil brazing material, a powder brazing material or a filamentary brazing material.

[0013] As a further optimization of the brazing connection method of tungsten alloy and molybdenum alloy of the present invention: the brazing material in step S2 includes the following components by mass percentage: Ti 16.38%, Zr 10.41%, Cr 11.86%, Cu 14.49% and the balance Ni.

[0014] As a further optimization of the brazing connection method of tungsten alloy and molybdenum alloy of the present invention: the thickness of the nickel foam in step S2 is 0.1 mm.

[0015] As a further optimization of the brazing connection method of tungsten alloy and molybdenum alloy of the present invention: the pore size of the foamed nickel is 110 ppi, the porosity is 80%, and the surface density is 270 g / m 2 , nickel purity is 99.5%.

[0016] As a further optimization of the brazing connection method of tungsten alloy and molybdenum alloy of the present invention: in the step S2, a pre-tightening force of 3 kPa is applied to the pre-brazed assembly after compaction.

[0017] As a further optimization of the brazing connection method of a tungsten alloy and a molybdenum alloy of the present invention: the brazing filler metal is a powder brazing filler metal prepared by mixing single substance powders, the particle size of the single substance powder is 20 to 100 μm, and the purity is ≥99.0%.

[0018] As a further optimization of the brazing connection method of tungsten alloy and molybdenum alloy of the present invention: the brazing temperature in step S3 is 900-1200°C.

[0019] As a further optimization of the brazing connection method of tungsten alloy and molybdenum alloy of the present invention, the step S3 is specifically as follows: placing the pre-brazed assembly in a vacuum brazing furnace at a vacuum degree of 5.0×10 -4 Pa, the temperature was raised to 600°C at a heating rate of 10°C / min and kept for 5 min, then raised to 1170°C at a heating rate of 5°C / min and kept for 10 min, then cooled to 100°C at a cooling rate of 10°C / min, and finally cooled to room temperature with the furnace, thus completing the brazing connection of tungsten alloy and molybdenum alloy.

[0020] The present invention has the following beneficial effects:

[0021] 1. The design concept of the solder composition used in the present invention is derived from the "cluster + atomic connection" structural model. The eutectic point Ni is selected based on the Ni-Ti binary phase diagram. 86.3 Ti 13.7 In order to suppress the brittleness of the joint, new elements are added on the basis of Ni-Ti. The added Cu element can generate CuTiNi 2 Intermetallic compound, which has extremely strong toughness and plasticity, CuTiNi in the brazing seam 2The presence of intermetallic compounds and Cu-based solid solutions can improve the plasticity and toughness of brazed joints. The added Cr, W, and Mo are atoms of the same main group and have similar chemical properties. The Cr element can generate a Cr(Mo) solid solution, which has high hardness and strength and can improve the mechanical properties of brazed joints. The added Zr is an active element that can promote the diffusion of elements in the joint and reduce the MoO 2 Segregation.

[0022] 2. The present invention adds a metal foam nickel intermediate layer during the brazing process. The foam material has good plastic deformation and can absorb residual strain energy. During the brazing cooling process, the foam nickel metal plays the role of a skeleton. During the solidification process of the solder, multiple melting zones solidify and shrink independently, and opposite shrinkage forces will be generated between adjacent melting zones, so that the stresses between adjacent small melting zones can be canceled. The addition of metal nickel foam has the effect of refining and diverting the solder, and the stress amplitude of each small melting zone is also reduced accordingly. When the stresses of all the small melting zones are superimposed on each other, the residual stress of the brazed joint is greatly relieved. At the same time, the Ti, Ni and Cu components in the solder are prone to produce compounds, and the foam nickel with a skeleton structure also has an adsorption effect, which makes CuTiNi 2 Concentrated in the center of the brazing seam, Cr and Mo are elements in the same period, and Cr (Mo) solid solution is easy to form. The thermal expansion coefficient of Cr (Mo) solid solution is almost the same as that of Mo. The residual stress in the heat-affected zone is eliminated, and the fracture position is transferred to the brazing seam area. The skeleton structure formed by the nickel foam changes the microstructure, the solid solution of Cu increases, and CuTiNi 2 It presents a skeleton shape, Cr(Mo) solid solution and (Ni,Cu) 2 (Ti, Zr) form a stable organizational structure in the skeleton, and the mechanical properties of the joint are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a physical picture of the welding sample of Example 1;

[0024] Figure 2 This is a microscopic morphology of the welded joint of Example 1;

[0025] Figure 3 This is the EDS surface scanning element analysis diagram of the welding joint in Example 1;

[0026] Figure 4 This is a microscopic morphology of the joint fracture of Example 1;

[0027] Figure 5 This is a microscopic morphology of the welded joint of Example 2;

[0028] Figure 6 This is a microscopic morphology of the welded joint of Example 3;

[0029] Figure 7 This is the microscopic morphology of the welded joint of Comparative Example 4;

[0030] Figure 8 EDS surface scanning element analysis diagram of the welded joint of Comparative Example 4;

[0031] Fig. 9 This is the microscopic morphology of the joint fracture of Comparative Example 4;

[0032] Fig.10 This is the element analysis diagram of the joint fracture of Comparative Example 4;

[0033] Fig.11 This is the XRD pattern of the joint fracture of Comparative Example 4;

[0034] Fig.12 This is the microscopic morphology of the welded joint of comparative example 5. DETAILED DESCRIPTION

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the content of the present invention is not limited to the following embodiments.

[0036] <Example 1>

[0037] The solder of this embodiment has the following components by mass percentage: Ti 16.38, Zr 10.41, Cr 11.86, Cu 14.49 and the balance Ni. The selected single-substance powder solder is a spherical powder with a particle size of 50 microns and a purity greater than 99.0%. The single-substance powders of Ni, Ti, Zr, Cr and Cu are mixed in proportion and ball-milled for five hours.

[0038] The nickel foam is commercial nickel foam with a thickness of 0.1 mm and a pore density of 110 ppi.

[0039] The size of the WCu alloy and TZM alloy base materials is 5×5×5 mm 3 10×10×3 mm 3 The selected single powder solder is spherical powder with a particle size of 50 microns. The size of the prefabricated nickel foam is 5×5×0.1 mm 3 , pore size is 110 ppi, porosity is 80%, and surface density is 270 g / m 2 , nickel purity is 99.5%.

[0040] Welding process: The surfaces of WCu alloy and TZM alloy were ground and polished, ultrasonically cleaned with anhydrous ethanol for 30 minutes and then air-dried, the brazing material was spread between the two alloy plates, the nickel foam was placed between the brazing material and the molybdenum alloy, and a pressure of 3 kPa was applied above the assembly to obtain a pre-brazed assembly. The pre-brazed assembly was placed in a vacuum brazing furnace with a vacuum degree of 5 × 10 - 4 Pa, in the first stage, the temperature was raised to 600 °C at a rate of 10 °C / min and then kept for 5 min to make the sample evenly heated. In the second stage, the temperature was raised to 1170 °C at a rate of 5 °C / min and kept for 10 min. In the third stage, the temperature was lowered to 100 °C at a rate of 10 °C / min and finally cooled to room temperature with the furnace to complete the welding. The welded sample is as follows Figure 1 shown.

[0041] The shear strength of the welded samples was tested using a UTM-2460 electronic universal testing machine, and the average shear strength was 279.42 MPa.

[0042] like Figure 2 and 3 As shown in the figure, the microstructure of the welded joint and the EDS surface scanning element analysis diagram. Figure 4 The following are the microscopic morphology of the joint fracture, where (b) and (c) are the enlarged microscopic morphology of points A and B in (a). The microstructure of the tungsten alloy and molybdenum alloy welded joint is good, and the brazing seam is mainly composed of Cr(Mo) solid solution, (Ni,Cu) 2 (Ti, Zr), CuTiNi 2 phase and a small amount of Cu solid solution composition; the streaks caused by the intergranular penetration behavior in the heat affected zone of the molybdenum alloy are effectively suppressed, the residual stress concentration problem is weakened, and the toughness and strength of the joint are effectively improved.

[0043] During the cooling process, due to the small thermal expansion coefficient of tungsten alloy and molybdenum alloy, the thermal expansion coefficient of nickel-based solder is large, the solder volume shrinks greatly, and the volume change of tungsten alloy and molybdenum alloy is small. At this time, large residual stress is easily generated at the connection position between the solder and the substrate. The striped CuTiNi 2 The thermal expansion coefficients of intermetallic compounds and Mo alloy matrix do not match. Turner model is used to calculate the thermal expansion coefficients of CuTiNi 2 The thermal expansion coefficient is 12.7×10 -6 / K, obvious residual stress concentration appears in the heat-affected zone of the molybdenum alloy, and the starting position of the fracture is generated. This is also the reason why the fracture occurs in the heat-affected zone of the molybdenum alloy base material when there is no foam nickel intermediate layer.

[0044] When the metal nickel foam intermediate layer is added, the foam material has good plastic deformation and can absorb residual strain energy. During the brazing cooling process with the addition of the nickel foam metal intermediate layer, the nickel foam metal plays the role of a skeleton. During the solidification process of the brazing material, the nickel foam metal flows into the nickel foam and becomes multiple melting zones that independently solidify and shrink. Opposite shrinkage forces will be generated between adjacent melting zones, so that the stresses between adjacent small melting zones can be canceled. Therefore, the addition of metal nickel foam has the effect of refining and diverting the brazing material, and the stress amplitude of each small melting zone is also reduced accordingly. When the stresses of all the small melting zones are superimposed on each other, the residual stress of the brazed joint is greatly relieved. Ti, Ni and Cu in the brazing material are extremely easy to produce compounds, and the nickel foam with a skeleton structure also has an adsorption effect, which makes CuTiNi 2 Concentrated in the center of the brazing seam, Cr and Mo are elements in the same period, and Cr(Mo) solid solution is easy to form. The thermal expansion coefficients of Cr and Mo are extremely similar. After substituting into the Turner model, the thermal expansion coefficient of the Cr(Mo) solid solution is almost the same as that of Mo. The residual stress in the heat-affected zone is eliminated, and the fracture position is transferred to the brazing seam area. The microstructure in the brazing seam area is still Cr(Mo) solid solution, (Ni,Cu) 2 (Ti, Zr), CuTiNi 2 The skeleton structure formed by nickel foam changes the microstructure, the solid solution of Cu increases, and the CuTiNi 2 It presents a skeleton shape, and the Cr(Mo) solid solution and (Ni,Cu)2(Ti,Zr) form a stable organizational structure in the skeleton, and the mechanical properties of the joint are greatly improved.

[0045] <Example 2>

[0046] This embodiment is basically the same as embodiment 1, except that the brazing temperature of this embodiment is adjusted to 1150°C. After the welding is completed, the shear strength of the welded sample is tested using a UTM-2460 electronic universal testing machine, and the average shear strength is 213.23 MPa. Figure 5 The microscopic morphology of the welded joint is shown in Figure 2.

[0047] <Example 3>

[0048] This embodiment is basically the same as embodiment 1, except that the brazing temperature of this embodiment is adjusted to 1190°C. After the welding is completed, the shear strength of the welded sample is tested using a UTM-2460 electronic universal testing machine, and the average shear strength is 241.38 MPa. Figure 6 The microscopic morphology of the welded joint is shown in Figure 2.

[0049] <Example 4>

[0050] This embodiment is substantially the same as the embodiment 1, except that the solder of this embodiment comprises, by mass percentage, Ti 17.98, Zr 10.01, Cr 11.86, Cu 14.01, and the balance Ni.

[0051] <Example 5>

[0052] This embodiment is substantially the same as the embodiment 1, except that the solder of this embodiment comprises, by mass percentage, Ti 15.01, Zr 10.98, Cr 11.01, Cu 14.99 and the balance Ni.

[0053] <Example 6>

[0054] This embodiment is basically the same as the embodiment 1, except that: the brazing process of this embodiment is as follows: the pre-brazed assembly is placed in a vacuum brazing furnace at a vacuum degree of 5.0×10 -4 Pa, the temperature was increased to 650 °C at a heating rate of 8 °C / min and kept at this temperature for 5 min, then increased to 1170 °C at a heating rate of 4 °C / min and kept at this temperature for 5 min, then cooled to 110 °C at a cooling rate of 8 °C / min, and finally cooled to room temperature with the furnace.

[0055] <Example 7>

[0056] This embodiment is basically the same as the embodiment 1, except that: the brazing process of this embodiment is as follows: the pre-brazed assembly is placed in a vacuum brazing furnace at a vacuum degree of 5.0×10 -4 Pa, the temperature was increased to 550 °C at a heating rate of 12 °C / min and kept at this temperature for 10 min, then increased to 1170 °C at a heating rate of 6 °C / min and kept at this temperature for 10 min, then cooled to 90 °C at a cooling rate of 12 °C / min, and finally cooled to room temperature with the furnace.

[0057] <Comparative Example 1>

[0058] This comparative example uses Ti-28Ni brazing filler metal to braze TZM alloy and WCu alloy. The sizes of TZM alloy and WCu alloy are 10×10×3 mm 3 and 4×4×5 mm 3, Ti-28Ni (wt%) was first vacuum melted 10 times with Ti wire and Ni, and then processed into foil with a thickness of about 100 microns. The welding process is as follows: heat to 1000 ℃ at a rate of 20 ℃ / min, and keep for 10 minutes to maintain a uniform temperature distribution. Heat to brazing temperature at a rate of 10 ℃ / min, and keep at brazing temperature for 10 minutes. Finally, slowly cool to 200 ℃ at a rate of 5 ℃ / min. At the brazing temperature of 1040 ℃, the optimal shear strength of the sample at room temperature reaches 125.3MPa.

[0059] <Comparative Example 2>

[0060] This comparative example uses Ti-61Ni brazing filler metal to braze TZM alloy and WCu alloy. The sizes of TZM alloy and WCu alloy are 10×10×3 mm 3 and 4×4×5 mm 3 , Ti-61Ni (wt%) was first vacuum melted 10 times with Ti wire and Ni, and then processed into foil with a thickness of about 100 microns. The welding process is as follows: heat to 1000 ℃ at a rate of 20 ℃ / min, and keep for 10 minutes to maintain a uniform temperature distribution. Heat to brazing temperature at a rate of 10 ℃ / min, and keep at brazing temperature for 10 minutes. Finally, slowly cool to 200 ℃ at a rate of 5 ℃ / min. At the brazing temperature of 1240 ℃, the optimal shear strength of the sample at room temperature reaches 128.1MPa.

[0061] <Comparative Example 3>

[0062] This comparative example uses Ti-50Ni brazing filler metal to braze TZM alloy and WCu alloy. The sizes of TZM alloy and WCu alloy are 10×10×3 mm 3 and 4×4×5 mm 3 , Ti-50Ni (wt%) was first vacuum melted 10 times with Ti wire and Ni, and then processed into a foil with a thickness of about 100 microns. The welding process is as follows: heat to 1000 ℃ at a rate of 20 ℃ / min, and keep for 10 minutes to maintain a uniform temperature distribution. Heat to brazing temperature at a rate of 10 ℃ / min, and keep at brazing temperature for 10 minutes. Finally, slowly cool to 200 ℃ at a rate of 5 ℃ / min. At the brazing temperature of 1340 ℃, the optimal shear strength of the sample at room temperature reaches 131.6MPa.

[0063] <Comparative Example 4>

[0064] This comparative example is basically the same as Example 1, except that: in this comparative example, no foam nickel intermediate layer is added during the brazing process, and the brazing temperature is adjusted to 1130°C.

[0065] After welding, the shear strength of the welded samples was tested using a UTM-2460 electronic universal testing machine, and the average shear strength was 157.29 MPa. Figure 7 and 8 As shown in the figure, the microstructure of the welded joint and the EDS surface scanning element analysis diagram. Fig. 9 As shown in the figure, the fracture microscopic morphology of the joint, where (b) and (c) are the enlarged microscopic morphology of points A and B in (a). Fig.10 As shown in Figure 1, this is the element analysis diagram of the joint fracture. Fig.11 Shown is the XRD pattern of the joint fracture.

[0066] Combined with the EDS analysis of the brazing seam and the XRD analysis of the fracture, it can be seen that the brazing seam is mainly composed of Cr(Mo) solid solution, (Ni,Cu) 2 (Ti, Zr), CuTiNi 2 phase and a small amount of Cu solid solution; the heat affected zone of the molybdenum alloy is mainly composed of the typical striped CuTiNi 2 Intermetallic compounds, Cr(Mo) solid solutions and molybdenum alloy parent materials.

[0067] From the fracture morphology of the joint, it can be seen that the fracture surface is divided into two parts. From the fracture element distribution diagram, it can be seen that one part of the fracture is the Mo matrix and the other part is the solder component. The fracture path starts from the stripes formed by the intergranular penetration stress and extends to the center of the weld and the Mo alloy matrix. The fracture morphology of the Mo matrix is ​​as follows: Fig. 9 As shown in (b), it has river-like texture and cleavage steps, which is judged to be a cleavage fracture mode. The fracture mode of the weld center is as follows Fig. 9 As shown in (c), the obvious dimple shape can be judged as a ductile fracture mode. Compared with the brittle fracture mode of the conventional Ni-Ti based brazing filler metal brazed tungsten / molybdenum alloy joint, this comparative example is a mixed fracture mode of cleavage fracture and ductile fracture. 2 Intermetallic compounds improve joint toughness and strength.

[0068] <Comparative Example 5>

[0069] This comparative example is basically the same as Example 1, except that: in this comparative example, no foam nickel intermediate layer is added during the brazing process, and the brazing temperature is adjusted to 1150°C. After the welding is completed, the shear strength of the welded sample is tested using a UTM-2460 electronic universal testing machine, and the average shear strength is 148.55MPa. Fig.12 The microscopic morphology of the welded joint is shown in Figure 2.

[0070] It can be seen from <Comparative Examples 1-5> that, compared with the traditional Ni-Ti based solder, the present invention improves the shear strength by adding three new elements, Zr, Cr and Cu, to improve the intermetallic compound.

[0071] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A brazing connection method for tungsten alloy and molybdenum alloy, characterized in that: The following steps are involved: S1: pre-treating tungsten alloy base material and molybdenum alloy base material; S2: placing the brazing filler metal between the tungsten alloy base material and the molybdenum alloy base material, placing the nickel foam between the brazing filler metal and the molybdenum alloy base material, and compacting them to obtain a pre-brazed assembly; Among them, the composition of the brazing material is Ni rest Ti a Zr b Cr c Cu d , 15≤a≤18wt%; 10≤b≤11wt%; 11≤c≤12wt%; 14≤d≤15wt%; the rest is Ni; The pore size of the nickel foam is 110 ppi, the porosity is 80%, and the surface density is 270 g / m 2 , nickel purity is 99.5%; S3: Place the pre-brazed assembly in a vacuum brazing furnace at a vacuum degree of 5.0×10 -4 Pa, heat up to 550-650℃ at a heating rate of 8-12℃ / min and keep warm for 5-10min, then heat up to 900-1200℃ at a heating rate of 4-6℃ / min and keep warm for 5-10min, then cool to 90-110℃ at a cooling rate of 8-12℃ / min, and finally cool to room temperature with the furnace to complete the brazing connection of tungsten alloy and molybdenum alloy.

2. A brazing connection method for tungsten alloy and molybdenum alloy as claimed in claim 1, characterized in that: The step S1 specifically comprises: grinding the welding surfaces of the tungsten alloy parent material and the molybdenum alloy parent material with sandpaper, then immersing the ground parent materials in anhydrous ethanol for ultrasonic cleaning for 25 to 35 minutes, and finally air-drying.

3. A brazing connection method for tungsten alloy and molybdenum alloy as claimed in claim 1, characterized in that: The solder in step S2 is foil solder, powder solder or wire solder.

4. A brazing connection method for tungsten alloy and molybdenum alloy as claimed in claim 1, characterized in that: The solder in step S2 includes the following components by mass percentage: Ti 16.38%, Zr 10.41%, Cr 11.86%, Cu 14.49% and the balance Ni.

5. A brazing connection method for tungsten alloy and molybdenum alloy as claimed in claim 1, characterized in that: The thickness of the nickel foam in step S2 is 0.1 mm.

6. A brazing connection method for tungsten alloy and molybdenum alloy as claimed in claim 1, characterized in that: In the step S2, a pre-tightening force of 3 kPa is applied to the pre-soldering assembly after compaction.

7. A brazing connection method of tungsten alloy and molybdenum alloy as claimed in claim 3, characterized in that: The solder is a powder solder made by mixing simple powders, the particle size of the simple powders is 20-100 μm, and the purity is ≥99.0%.

8. A brazing connection method for tungsten alloy and molybdenum alloy as claimed in claim 1, characterized in that: The step S3 specifically includes placing the pre-brazed assembly in a vacuum brazing furnace at a vacuum degree of 5.0×10 -4 Pa, the temperature was raised to 600°C at a heating rate of 10°C / min and kept for 5 min, then raised to 1170°C at a heating rate of 5°C / min and kept for 10 min, then cooled to 100°C at a cooling rate of 10°C / min, and finally cooled to room temperature with the furnace, thus completing the brazing connection of tungsten alloy and molybdenum alloy.

Citation Information

Patent Citations

  • Nickel-based amorphous brazing filler metal and preparation method and application thereof

    CN116851958A

  • Nickel-based diamond composite coating as well as preparation method and application thereof

    CN118854276A